Logistics workers and global logistics: the heavy lifters of globalisation. (1st October 2010) - Roger Sealey
Abstract : This article examines the growing importance of logistics and logistics workers, the growth of offshoring and the changing balance between manufacturers and retailers in the post-Fordist era due in part to the bar code. It explores the interdependent relationship between technological innovation, globalisation and the expansion of the logistics sector and the impacts of time-space compression on logistics work, before examining the vulnerabilities created in global supply chains by these interdependencies. It concludes that the central place of distribution in a global economy confers a new strategic power on logistics workers.